TƯƠNG TÁC GIỮA VỎ VÀ NỀN SAN HÔ DƯỚI TÁC DỤNG CỦA TẢI TRỌNG NỔ - Chung, Nguyễn Thái (Vietnam Journal of Marine Science and Technology, 2012)
In this study, the author present the calculating method for and some results studying interaction between cylindrical shell and coral foundation of Truong Sa archipelago under blast loading. The problem analysis  with finite element method and using  shell element (for shell structure), solid element (for coral foundation), 3D slip element (for layer between shell structure and coral foundation). The paper results can be used in design as reference for shell structures in the coral foundation under static and dynamic loading.